A comprehensive study of the differences in protein expression and chemical constituents in tea leaves (Camellia sinensis var. sinensis) with different maturity using a combined proteomics and metabolomics method. (July 2022) - Sun, Zhen; Chen, Dan; Zhu, Liyao; Zhao, Yanni; Lin, Zhi; Li, Xianzhen; Dai, Weidong
Graphical abstract: Highlights: A combined metabolomics and proteomics study on tea leaves with different maturity. 112 metabolites significantly differ among the bud, 1st-4th leaves, and stem. Photosynthesis, glycolysis, TCA cycle, amino acids, and flavonoids differed. Enhanced biosynthesis of amino acids, flavanols, and related enzymes in bud. Higher expression of FLS led to higher levels of flavonol glycosides in 1st leaf. Abstract: The maturity of tea leaves has a great influence on the flavor quality and commercial price of tea. In this work, a combined proteomics and metabolomics analysis was applied to investigate the differences in protein expression and metabolites among tea leaves with different maturity. Integrated analysis showed that there were significant differences in 112 nonvolatile components related to the pathways of photosynthesis, glycolysis, tricarboxylic acid cycle, and the biosynthesis of amino acids, phenylpropanoids and flavonoids. The bud had higher expression levels of most enzymes related to the biosynthesis of amino acids, phenylpropanoids, and flavonoids, leading to higher levels of amino acids, most flavanols, and procyanidins compared with the leaves. The 1 st leaf showed a higher expression level of flavonol synthase, which produces higher levels of flavonol-3-glycosides. This study offers deep insight into the maturity of tea at both the protein and metabolite levels and provides a guideline for tea manufacturing.